Unravelling the role of parliament in developing network industries: comparative case of ICT sector reform in Kenya and South Africa - Matanga, Cecilia Rudo (Research of GSB, 2017)
Several scholars have identified institutional and regulatory conditions under which Information Communication Technologies (ICT) reforms can accomplish positive public policy outcomes. This literature pays little attention, however, to the role of parliaments in these reforms. The institutional factors determining the degree and nature of parliamentary participation in ICT sector reforms in Africa is what this thesis examines. Drawing from the political economy tradition, this thesis explores the interplay between the executive, the parliament and the various sectoral interests that determine ICT sector reforms in developing countries. It does so by placing parliament in a conceptual framework that combines the concept of ICT as a complex ecosystem with that of a constellation of institutions. The gathered empirical evidence is studied through this conceptual lens to build the cases of parliamentary participation in Kenya and South Africa - two of the most dynamic ICT markets in sub-Saharan Africa - which are then analysed comparatively. Some of the information is gathered through a self-assessment survey by members of the ICT parliamentary committees and complemented by high-level interviews with the main sector players. The findings are triangulated with those from an extensive document analysis. This thesis contextualises institutional analysis in specific political circumstances of the two countries in order to understand the relevance of parliament in sector reforms. The findings have important implications for our understanding of structural and institutional constraints on parliaments in developing countries and nascent democracies. Parliaments lack capacity to simply fulfill their legislative and oversight roles, let alone creating an enabling environment for innovative public policy, sector investment and public interest outcomes as required by this dynamic sector in any modern, globalised economy. Systematic coding of the data revealed national governance and institutional arrangements as key determinants of an ICT ecosystem that adapts to local and international conditions, confirming parliament as not simply a neutral legal structure but a significant power broker, reflecting competing interests at play. The formal legal system in both countries is uneven and underutilized, ineffective in achieving robustly-contested public interest outcomes. In order to manage political interests, parliament structures and serves principal agent-relationships, vetoes ICT policy and decision-making processes, links interest groups to government and party agendas, resolves conflicts and, sometimes, builds consensus among key players. The examination of institutional designs of both parliaments identifies critical capacity deficits that are at the heart of the negative outcomes in national legislative and oversight processes. In South Africa, the reason for these deficits is primarily that the parliamentary system promotes political party and executive dominance, which undermine multi-party and participatory structure of parliamentary processes to achieve party preferences and control outcomes. In Kenya, whilst the combination of distinct separation of powers and a constituency-based electoral system provides a legal basis for greater parliamentary accountability, the highly fragmented sector arrangements compounded by lack of internal capacity to utilize parliamentary instruments and mechanisms constrain parliament's participation. These weak institutional arrangements and designs, in both Kenya and South Africa, limit independence of parliament from the executive and sometimes industry, compromising the parliamentary oversight and visionary leadership expected from specialized portfolio committees. This calls for a transformation of arrangements to uphold and reinforce constitutional mandates that give parliament the power and ability to fulfill its role in policy reforms.